Research on the Strategy of Photovoltaic Grid-connected Generation and Reactive Power Regulation - ZHAO Xianggui; WU Hengliang; CHEN Yifeng; WANG Nan (Kongzhi Yu Xinxi Jishu)
It designed a photovoltaic (PV) grid-connected power conditioner system integrating grid-connected generation and reactive power regulation , in which the PV grid-connected inverter can provide active power for grid and output reactive power which the grid demand. System mathematic model, control structure and reactive power control method were discussed and the limit of reactive power output was calculated. Based on the communication protocol of PV power station, the uniformed control of reactive power regulation and PV gridconnected generation has been implemented in the prototype of 500 kW photovoltaic grid-connected inverter. Simulation results show that the PV power station can output reactive power to support voltage of PCC(point of common coupling) when faults happen and can improve the stability of local grid voltage.